Board effectiveness in corporate crises: lessons from the evolving empirical research. Issue 4 (29th July 2014) - Abatecola, Gianpaolo; Farina, Vincenzo; Gordini, Niccolò
Abstract : Purpose: – This article aims to comment on how the empirical research on board effectiveness in crisis contexts has been evolving over time. Over the years, the empirical evidences have demonstrated that particular board features can improve the survival chances of firms suffering a crisis and, to date, experts agree that discussing these evidences is necessary for the further improvement of knowledge in this field. Design/methodology/approach: – This is a critical review article. Findings: – Valuable evidences emerge from the review. For example, it seems that board independence has a key role in enhancing the performance of firms suffering a crisis. At the same time, the review suggests that further refinement is needed for supporting (or eventually refuting) the idea that boards and/or Chief Executive Officers (1) must be replaced to achieve successful turnaround strategies. Originality/value: – On the basis of its findings, the review also prospects a number of conceptual and methodological implications for the future research and practice about board effectiveness in corporate crises. For example, these implications are associated with future investigations about the executives' sociodemographic features and personality traits as well. More international comparisons seem also needed to improve the reliability of the extant knowledge.